Need fulfillment and experiences on social media: A case on Facebook and WhatsApp - Karapanos, Evangelos; Teixeira, Pedro; Gouveia, Rúben (My University, 2016)
With an increasing inflow and outflow of users from social media, understanding the factors the drive their adoption becomes even more pressing. This paper reports on a study with 494 users of Facebook and WhatsApp. Different from traditional uses & gratifications studies that probe into typical uses of social media, we sampled users' single recent, outstanding (either satisfying or unsatisfying) experiences, based on a contemporary theoretical and methodological framework of 10 universal human needs. Using quantitative and qualitative analyses, we found WhatsApp to unlock new opportunities for intimate communications, Facebook to be characterized by primarily non-social uses, and both media to be powerful lifelogging tools. Unsatisfying experiences were primarily rooted in the tools' breach of offline social norms, as well in content fatigue and exposure to undesirable content in the case of Facebook. We discuss the implications of the findings for the design of social media.
Keywords: Human needs; User experience; Facebook; WhatsApp